2021
DOI: 10.2147/ijgm.s335162
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Investigation of Competing Endogenous RNA Networks and Candidate Genes Involved in SARS-CoV-2 Infection

Abstract: Introduction:The current COVID-19 pandemic caused by a novel coronavirus SARS-CoV -2 is a quickly developing global health crisis, yet the mechanisms of pathogenesis in COVID-19 are not fully understood. Methods:The RNA sequencing data of SARS-CoV-2-infected cells was obtained from the Gene Expression Omnibus (GEO). The differentially expressed mRNAs (DEmRNAs), long non-coding RNAs (DElncRNAs), and microRNAs (DEmiRNAs) were identified by edgeR, and the SARS-CoV-2-associated competing endogenous RNA (ceRNA) net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…IFI6 (also known as G1P3, ISG16, or IFI6-16) has been previously described as an IFN-induced gene ( 36 , 37 ), which is induced by infection of many RNA viruses such as influenza ( 38 ), flaviviruses ( 15 , 17 ) and SARS-CoV-2 ( 39 ). To confirm that IFI6 is an ISG in our cell culture systems, epithelial human lung adenocarcinoma-derived A549 cells were treated with poly(I:C), an analog of dsRNA, or with IFNα, for 16 h, and the levels of IFI6 were measured by RT-qPCR, and compared to the levels in mock-treated cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IFI6 (also known as G1P3, ISG16, or IFI6-16) has been previously described as an IFN-induced gene ( 36 , 37 ), which is induced by infection of many RNA viruses such as influenza ( 38 ), flaviviruses ( 15 , 17 ) and SARS-CoV-2 ( 39 ). To confirm that IFI6 is an ISG in our cell culture systems, epithelial human lung adenocarcinoma-derived A549 cells were treated with poly(I:C), an analog of dsRNA, or with IFNα, for 16 h, and the levels of IFI6 were measured by RT-qPCR, and compared to the levels in mock-treated cells.…”
Section: Resultsmentioning
confidence: 99%
“…IFI6 is an ISG whose expression is induced by many viruses ( 15 , 17 , 38 , 39 ), such as IAV ( Figure 1C ), and SARS-CoV-2 ( Figure 1D ). Many ISGs display antiviral functions ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that IFIT2 and IFI44L are strongly induced in bronchoalveolar lavage (BAL) cells and peripheral blood mononuclear cells (PBMCs) of COVID-19 patients, leading to enhance antiviral and immune modulatory functions (Zhu et al 2020 ; Shaath et al 2020 ). Transcriptome analysis of PBMCs also highlighted the potential role of IFI6 in responses to SARS-COV-2 in comparison to other respiratory viruses (Shaath et al 2020 ; Qi et al 2021 ). According to our findings, IL1R2 is a downregulated NP marker for COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…IFI6 is induced by interferon, and the IFI6 protein may be involved in the regulation of cell apoptosis ( Jia et al, 2020 ). Researchers compared and analyzed the transcriptional data of cells with SARS-CoV-2 and other viral infections and found that IFI6 may be a potential target for intervention in COVID-19 ( Qi et al, 2021 ). IFI6 can protect uninfected cells by preventing virus-induced endoplasmic reticulum invagination ( Richardson et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%